Can Teaching Enthusiasm Partially Predict the Reading Attainment of Low-income Students in Secondary Schools in England? - Chen, Wenqing (School of Education, Durham University, 2025)
The poverty achievement gap in early reading is a persistent issue in England and around the world, potentially disadvantaging poor students and their further study. This new study employs student-perceived teaching enthusiasm and reading attitudes to help explain the poverty attainment gap. The sample was 5,242 15-year-old participants in PISA 2018 from 175 secondary schools in England. Path analysis is used to investigate the potential effect of teaching enthusiasm on the reading attainment of low-income students. The findings indicate that family socioeconomic status remains an important predictor of students' reading achievement. Students from economically privileged families tend to rate teaching enthusiasm more highly and express a positive reading attitude, which can partially explain the poverty attainment gap in reading. Therefore, teachers might be able to enhance low-income students’ reading outcomes and close the poverty attainment gap a little through enhanced teaching enthusiasm to cultivate students’ positive reading attitudes.
EPrint Processing Status: Full text deposited in DRO